Impact of Computed Tomography on Operative Planning for Ankle Fractures Involving the Posterior Malleolus. (December 2017) - Donohoe, Steven; Alluri, R. Kiran; Hill, J. Ryan; Fleming, Mark; Tan, Eric; Marecek, Geoffrey
Background: The purpose of this study was to (1) Determine the effect of computed tomography (CT) on identification of fractures involving the posterior malleolus, (2) determine its effect on operative indications, and (3) determine its effect on the overall operative plan. Methods: Patients with ankle fractures involving the posterior malleolus were identified. Only injuries with complete preoperative plain radiographs and a CT scan were included. Spiral tibia fractures and pilon variants were excluded. The plain radiographs were deidentified, randomized, and presented to 3 orthopedic surgeons. They were asked 3 questions: (1) Is this fracture simple or complex? (2) Does the injury require direct visualization and reduction? and (3) How would you position the patient and approach the fracture? The same process was repeated for the CT scans. A total of 376 posterior malleolus injuries were identified and 25 met the inclusion criteria. Results: A complex fracture pattern was identified on 44% of plain radiographs and 56% of CT scans. The surgeons chose to operate in 84% of cases based on plain radiographs and 92% of cases based on CT scan. The observers changed their operative approach or positioning 44% of the time after reviewing CT images. The interobserver and intraobserver correlation coefficients were moderate. Conclusion: The use of CT scan changed operative positioning and approach in 44% of cases. There was no significant change in characterization or operative indications when comparing plain radiographs to CT scan. CT scan may be a valuable tool in the management of ankle fractures involving the posterior malleolus. Level of Evidence: Diagnostic Level III, comparative series.